Educational Issues and Challenges in the 21st century of India: Examining the Educational System and Teacher Characteristics in 21st Century India (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The article tries to introduce issues and challenges of the 21st century in India. Here thequestion arise that, “ facing a complex set of global threats to our future, how do we find a way forward?Things are changing very rapidly in every dimensions globally. If we talk about the challenges we faces in21st century, there are Social challenges, Economical challenges, Political challenges, Environmentalchallenges, and many more. But one of the most critical challenges we face today as student is ineducational field. Things are changing in our education system very quickly. Now the world isinterconnected with the advance technologies, and the new generation have there upbringing with thesetechnologies and social platform. Further more changes in the needs of the society and the appearanceof new jobs, all together demand a revision in the educational system reveals that to win public trust,training admirable teachers is very important – Roger Kaufman believes that the rate of success in aneducational system depends on the compatibility of the goals of the system and the goals off thesociety.So, the following questions are going to be discussed in this article. How is the education system is in 21st century? What are the characteristic of teachers in 21st century?